2015
DOI: 10.1017/s1431927615014750
|View full text |Cite
|
Sign up to set email alerts
|

A Compact “Water Window” Microscope with 60 nm Spatial Resolution for Applications in Biology and Nanotechnology

Abstract: Short illumination wavelength allows an extension of the diffraction limit toward nanometer scale; thus, improving spatial resolution in optical systems. Soft X-ray (SXR) radiation, from "water window" spectral range, λ=2.3-4.4 nm wavelength, which is particularly suitable for biological imaging due to natural optical contrast provides better spatial resolution than one obtained with visible light microscopes. The high contrast in the "water window" is obtained because of selective radiation absorption by carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…The system is compact in size and makes possible wider collaboration in a multidisciplinary context with biologists, chemists, and scientists from other disciplines locally, in the university laboratories or companies. Moreover, such system offers higher spatial resolution to the visible light microscopes [17], [22] and do not require sample preparation like SEM microscopes. Although the spatial resolution achieved cannot compete with the SEM, it has to be EPJ Web of Conferences 167, 03002 (2018) https://doi.org/10.1051/epjconf/201816703002 PPLA 2017 noted that the SXR microscope still operates using photons instead of electrons.…”
Section: Discussionmentioning
confidence: 99%
“…The system is compact in size and makes possible wider collaboration in a multidisciplinary context with biologists, chemists, and scientists from other disciplines locally, in the university laboratories or companies. Moreover, such system offers higher spatial resolution to the visible light microscopes [17], [22] and do not require sample preparation like SEM microscopes. Although the spatial resolution achieved cannot compete with the SEM, it has to be EPJ Web of Conferences 167, 03002 (2018) https://doi.org/10.1051/epjconf/201816703002 PPLA 2017 noted that the SXR microscope still operates using photons instead of electrons.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 4 shows typical emission spectrum from nitrogen plasma in the 'water window' range (dashed line), generated by focused Nd:YAG laser pulse interacting with nitrogen/helium gas-puff target. The plot shows the H-like nitrogen line ( = 2.48 nm), attenuated by 200 nm thick Ti fi lter (dash-dotted line), and the He-like nitrogen line at  = 2.88 nm wavelength (solid line) used for imaging with the SXR microscope [18].…”
Section: Methodsmentioning
confidence: 99%
“…The geometrical magnification of the system was ~220x. It was already demonstrated that such system is capable to achieve a half-pitch spatial resolution of ~60nm [24]. More details about this work can be found in [25].…”
Section: Microscopy Systemsmentioning
confidence: 99%